Biomass feedstock transport using fuel cell and battery electric trucks improves lifecycle metrics of biofuel sustainability and economy. (10th January 2021) - Baral, Nawa Raj; Asher, Zachary D.; Trinko, David; Sproul, Evan; Quiroz-Arita, Carlos; Quinn, Jason C.; Bradley, Thomas H.
Abstract: The use of new vehicle technologies such as fuel cell hybrid electric and fully electric powertrains for biomass feedstock supply is an unexplored solution to reducing biofuel production cost, greenhouse gas emissions, and health impacts. These technologies have found success in light-duty vehicle applications and are in development for heavy-duty trucks. This study presents the first detailed stochastic techno-economic analysis and life-cycle assessment of biomass feedstock supply systems with diesel, fuel cell hybrid electric, and fully electric trucks and determines their impacts on biofuel production considering butanol as a representative biofuel. This study finds that fuel cell hybrid electric and fully electric trucks consume less energy relative to the diesel-powered truck regardless of the evaluated circumstances, including payloads of truck (loaded and empty), pavement types (gravel and paved), road conditions (normal and damaged), and road networks (local and highways). The use of fuel cell hybrid and fully electric trucks powered by H2 -fuel and renewable sources of electricity, respectively, results in a large reduction in cost and carbon footprint, specifically for a long-distance hauling, and minimize other economic and environmental impacts. While the economic advantage of fuel cell hybrid electric vehicle is dependent on the price of H2 -fuel and road conditions, use reduces the GHG emissions of biobutanol per 100 km-trucking-distance by 0.98–10.9 gCO2e /MJ. Results show that converting to fully electric truck transport decreases the biobutanol production cost and GHG emissions per 100 km-trucking-distance by 0.4–7.3 cents/L and 0.78 to 9.1 gCO2e /MJ, respectively. This study establishes the foundation for future investigations that will guide the development of economically, socially, and environmentally sustainable biomass feedstock supply system for cellulosic biorefineries or other goods transportation systems. Graphical abstract: Image 1 Highlights: Fuel economies of fully electric and fuel cell hybrid electric trucks are calculated. Cost and carbon footprint of delivering biomass with advanced trucks are quantified. Fully electric truck reduces butanol production cost in resource-rich areas by 1%. Selected advanced trucks reduce the carbon footprint of butanol by 11–25%. Economic and environmental benefits of advanced trucks increase with trucking distance.